2018
DOI: 10.20945/2359-3997000000016
|View full text |Cite
|
Sign up to set email alerts
|

Humoral hypercalcemia of pregnancy treated with bisphosphonates

Abstract: Hypercalcemia can be hazardous during pregnancy, most cases being due to primary hyperparathyroidism. We report a case of hypercalcemia with suppressed PTH levels necessitating treatment with bisphosphonates during pregnancy. A 38-year-old woman at the 26th week gestation was admitted because of symptomatic hypercalcemia. She did not take any medication that could influence her calcium levels. Physical examination was unremarkable. Laboratory tests on admission were: calcium 12.7 mg/dL (8.5-10.5 mg/dL), phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Although breastfeeding osteoporosis may be related to an increase in PTHrP, the specific mechanism of PTHrP leading to breastfeeding osteoporosis is still unclear (18). However, according to the correlation between PTHrP, breastfeeding osteoporosis, and hypercalcemia, we speculated that the treatment of lactation in this patient could reduce lactation and inhibit the secretion of PTHrP in the breast, which might improve hypercalcemia and its related symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…Although breastfeeding osteoporosis may be related to an increase in PTHrP, the specific mechanism of PTHrP leading to breastfeeding osteoporosis is still unclear (18). However, according to the correlation between PTHrP, breastfeeding osteoporosis, and hypercalcemia, we speculated that the treatment of lactation in this patient could reduce lactation and inhibit the secretion of PTHrP in the breast, which might improve hypercalcemia and its related symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…Authors, such as Sato [ 55 ], suggested that the PTHrP hypersecretion leading to hypercalcemia during pregnancy was of placental origin. Koren et al [ 57 ] presented a 38-year-old female without hypoparathyroidism developing hypercalcemia during pregnancy (12.7 mg/dL), alongside suppressed PTH; the authors suggested that this is likely due to PTHrP hypersecretion from the placenta (not measured) and noted significant resistance to conventional treatment (loop diuretics, isotonic saline, and calcitonin), requiring management with pamidronate (levels normalized postpartum). Of note, the authors do not mention whether the patient breastfed following delivery.…”
Section: Reviewmentioning
confidence: 99%
“…86 Case studies have reported the utility of BPs in pediatric hypercalcaemia secondary to Williams Syndrome 87 and in humor hypercalcaemia of pregnancy. 88 The antihypercalcaemic use of BPs is only discouraged in patients with renal failure, because the kidney is the main organ of BP elimination from the body (see the Pharmacology of Biphosphonates section), and it is already fragile in these patients due to the effort of calcium elimination. 85 Bone Scintigraphy.…”
Section: ■ Bisphosphonates In Clinical Practicementioning
confidence: 99%
“…Some of the patients that required repetition of treatment with BPs showed signs of drug resistance, with only partial reduction of calcium levels, but nonetheless they had significant improvements in symptomatology and increased lifespan . Case studies have reported the utility of BPs in pediatric hypercalcaemia secondary to Williams Syndrome and in humor hypercalcaemia of pregnancy . The antihypercalcaemic use of BPs is only discouraged in patients with renal failure, because the kidney is the main organ of BP elimination from the body (see the Pharmacology of Biphosphonates section), and it is already fragile in these patients due to the effort of calcium elimination…”
Section: Bisphosphonates In Clinical Practicementioning
confidence: 99%